What Happened to the Corporate Profit Tax? - Tom Karier (Levy Economics Institute of Bard College, 1990)
The radical reorientation of the federal budget during the 1980s provided generously for military expansion at the expense of pressing social needs. In the wake of such dramatic upheavals, the federal government will eventually be compelled to seek out new sources of revenue in order to compensate for the decade of neglect. But where will the resources be found to close the deficit, fully fund education, support the sick and impoverished, rebuild the infrastructure, and cleanup the environment? The Economic Policy Institute has placed a price tag of 65 billion on these necessities. As policy makers survey the revenue alternatives - military cuts, a more progressive income tax, a corporate take-over tax - one area they should not overlook is the corporate profit tax. Most people were aware that the corporate profit tax provided relatively little revenue in support of federal expenditures during the 1980s. But perhaps less well-known is the fact that corporations have enjoyed a steady decrease in their tax share for the past three decades. In 1960 corporate profit taxes financed approximately 22% of all expenditures by the federal government compared to only 7% in 1986. By exploring the reasons for this decline it becomes possible to appreciate the magnitude of the potential revenue that could be generated from corporate tax reform.
Keywords: 330